2017
DOI: 10.1002/ccd.27119
|View full text |Cite
|
Sign up to set email alerts
|

A novel lesion crossing technique: Balloon deployment using FORcible Manner (BADFORM) technique

Abstract: The efficacy and safety of the BADFORM technique might be acceptable. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…This device also could not pass the lesion; however, it modified the CTO entry-morphology (Figure 4(a)). After ELA ablation, the Caravel microcatheter (ASAHI Intecc) finally crossed the lesion using an antegrade approach with the BAlloon Deployment using FORcible Manner (BADFORM) technique [7] (Figure 4(b)), which enabled change of the wire from conventional the 0.014-inch wire to 0.009-inch RotaWire floppy (Boston Scientific) and RotaLink Plus 1.5mm burr ablation (Boston Scientific) (Figure 4(c)).…”
Section: Case Presentationmentioning
confidence: 99%
“…This device also could not pass the lesion; however, it modified the CTO entry-morphology (Figure 4(a)). After ELA ablation, the Caravel microcatheter (ASAHI Intecc) finally crossed the lesion using an antegrade approach with the BAlloon Deployment using FORcible Manner (BADFORM) technique [7] (Figure 4(b)), which enabled change of the wire from conventional the 0.014-inch wire to 0.009-inch RotaWire floppy (Boston Scientific) and RotaLink Plus 1.5mm burr ablation (Boston Scientific) (Figure 4(c)).…”
Section: Case Presentationmentioning
confidence: 99%
“…Nakabayashi et al reported the BADFORM technique for the treatment of BTK diseases. 5 This technique provides us with a strong backup force for lesion crossing. Considering this technique, after the guidewire externalization, the tail of the antegrade devices were fixed using a torque device.…”
Section: Discussionmentioning
confidence: 99%
“…Nakabayashi et al reported the BADFORM technique for the treatment of BTK diseases 5 . This technique provides us with a strong backup force for lesion crossing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, these labels readily suggest the potential and the inevitability of untoward events occurring during percutaneous revascularization of complex anatomy. The preceding report of 10 procedures did not result in significant complications despite its BADFORM name, however it was performed in only one center and only 10 patients needed this done over a span of 19 months .…”
mentioning
confidence: 97%